Read, Assume, and Label the Other: a Reading of the Short Story “Héroes a medio tiempo” by Justo Arroyo - Longan Phillips, Shirley (2018)
“Heroes a meido tiempo” is a short story of the Panamanian writer Justo Arroyo, winner of the Prize Premio Centroamericano de Literatura “Rogelio Sinán” 1997-1998. The objective of this paper is to read this short story from the perspective of the construction of the Other, by Luis Villoro. The text is told by an egocentric narrator who wants to be alone to ruminate about his own disgrace. However, a second man arrives and twists the story: the protagonist starts to read and label him; in other words, he constructs the second one as Other. Nevertheless, a dialogue arrives, forced at the beginning, which moves this “imponent” narrator from his discourse place. He goes out the bar sober, painless and with a new friend. The conclusion of this paper is that the protagonist arrives at the third and last stage of recognition of the Other because the pain has shortened the space between these two men, who are, just apparently, diﬀerent